Antithrombotic Effects Of Dextran Sulfate And Starch Sulfate Derivatives On Thrombosis Model Induced By Thromboplastin - Ortikov Mukhamadkodir Musajonovich; Nasirov Kabil Erkinovich; Raimova Guli Madmurodovna; Yusupova Umidaxon Raximovna; Jumanov Akhmadjon Mirzaevich; O’rinova Ozodaxon O’ktamovna; Abdullayeva Mavsumaxon Qoldoshevna; Bahrombekova Sojida Sherzodjonovna (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article demonstrates that dextran sulfate (D-38) and starch sulfate (K-39) derivatives are more effective in influencing the coagulation-platelet hemostasis system compared to heparin preparations in inducing thromboplastinemia in rats in vivo. This effect helps prevent the formation of thrombi in blood vessels.